SEROLOGY AND ANTIBIOTIC SUSCEPTIBILITY IN BRUCELLOSIS - AMARESH NIGUDGI; PRAVEEN DODDAMANI; VINAY HAJARE; SREEKANTHA; SUNIL BIRADAR; KANTHA R C (International Journal of Pharma and Bio Sciences, 2013)
Background and Objectives: Brucellosis is the most common disease noted among people who handle animals and human beings are indirectly infected. This study was aimed to know the serological profile and antibiotic susceptibility pattern in patients with brucellosis.Methodology and Results: 1120 patients with Pyrexia of unknown origin (PUO), among which 360 patients of high risk group having either history of contact with animals or their products were screened. 2% of cases revealed positively among the 1120 samples and 15.3% revealed positively among the 360 high risk group. Conclusion: Brucellosis is one of the important zoonotic disease usually diagnosed in patients with PUO. Serological screening will help in the accurate diagnosis and antibiotic susceptibility profile will help in the better treatment and limit the complications of brucellosis.